On determination of the stress-strain state of a multi-wedge system with thin radial defects under antiplane deformation = Określenie stanu naprężeń i przemieszczeń w układzie wieloklinowym z promieniowymi defektami przy ścinaniu wzdłużnym - Makhorkin, Mykola; Sulym, Heorhiy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An elastic isotropic multi-wedge system with radially located thin defects under longitudinal shear is considered. The procedure of construction of asymptotics of the stress and displacement fields in the vicinity of the system apex using the apparatus of generalized functions and Mellin transform is presented.
Keywords: naprężenia; ścinanie wzdłużne; defekty promieniowe; wedge system; angular point; singularity order; stress assymptotics; generalized stress intensity factor